Perilaku Pencarian Informasi Mahasiswa Tingkat Akhir Prodi Ilmu Hukum Universitas Andalas dalam Menyelesaikan Skripsi - Silvia, Rena (Universitas Negeri Padang, 2022)
Information Seeking Behavior is action taken by somebody in look for as well as browse information for fulfillment need information. This study aims to describe student information seeking behavior at the accessing stage, verifying, networking, and information management. The type of research is qualitative research using descriptive method. The research data were collected through interviews. The informants in this study were 8 final year students of the Legal Studies Study Program who were completing their thesis. The results of this study indicate that : (1) student information seeking behavior at the accessing stage in form of action; search information simple on google , access with keywords , setting up theme, access information from Instagram hashtags , easy and difficult access to ongoing information, identifying sources of information, accessing online databases. (2) Student information seeking behavior at the verifying stage in the form of action; check the title and content of the information, complete the information, the place where the information was published, check the introduction and background information, read the entire content of the information as needed, compare the information, see the year of publication , compare old knowledge with new knowledge. (3) Student information seeking behavior at the networking stage in the form of action; build relationships in the form of discussions with classmates, seniors, lecturers, and use the media for discussion. (4) Student information seeking behavior at the information managing stage in the form of action; download (download) information, group by type, create folders with special names, store information in WhatsApp groups.